Blockchain Technology and Islamic Legal Ethics: A Scrutiny of Authentic Deed Integrity in Sharia Economic Transactions - Perwitasari, Dita (TAWAZUN: Journal of Sharia Economic Law, 2026)
The development of digital technology today has brought about innovations that can support legal certainty in economic transactions, one of which is blockchain technology. In the context of sharia economic transactions, the existence of authentic deeds as legal documents has an important function in ensuring legality, authenticity, and protection of the rights of the parties. However, the challenge faced is the potential for manipulation, falsification, or uncertainty regarding the integrity of documents. This research addresses two main issues: first, how blockchain technology aligns with Islamic legal ethics in ensuring the integrity of authentic deeds; second, how effective its application is in Islamic economic transactions in Indonesia. This study aims to examine the relationship between blockchain technology and Islamic legal principles, as well as analyze the prospects of its implementation in strengthening the authenticity of deeds. The research method used is normative legal research with a legislative, conceptual, and comparative approach. The results show that blockchain has characteristics that support maqāṣid al-syarī‘ah, particularly the principles of justice, transparency, and honesty, through a permanent, decentralized, and tamper-proof recording system. The implementation of blockchain in sharia economic transactions has the potential to increase the integrity of authentic deeds and public trust, although it is still necessary to strengthen national regulations, especially harmonization with the Notary Law and sharia financial regulations. Thus, the integration of this technology can be a modern instrument to strengthen legal protection while maintaining compliance with Islamic legal ethics.